"We're Not Giving This Child Back To Lesbians": An Examination of LGBTQ+ Parents' Loss of Children to the Family Regulation System - McGowan, Grace (Columbia Journal of Gender and Law, 2024)
"We're Not Giving This Child Back To Lesbians": An Examination of LGBTQ+ Parents' Loss of Children to the Family Regulation System